Plan de negocios para el aprovechamiento del acuerdo de Cartagena para la industrialización y exportación de snacks de kiwi con chocolate para ser comercializados en la ciudad de Lima – Perú - Cuadrado Ponce, Carlos Danilo (2020)
This project is carried out in order to analyze the feasibility of creating a snack that has kiwi and chocolate, thanks to its properties, the final product points to healthier consumption trends. It will be produced in Los Ríos - Ecuador to export to Lima - Peru, taking advantage the CAN trade agreements. The analysis of the industry is carried out using the PEST tools, determining opportunities and threats in both environments and PORTER to determine the analysis of the industry itself. Thanks to qualitative research (interviews with experts in the industry and potential Peruvian consumers) and quantitative research (surveys to Inhabitants of Lima), it was possible to determine important data regarding the environment. With all the information collected, the marketing plan is designed to prove the commercial strategies that mitigate possible threats and to establish the correct marketing mix: price, product, place and promotion in order to establish the best strategies to position the brand in the market and in the consumers’ minds. The business opportunity presents some advantages for the implementation of this project, thanks to the fact that, firstly, no company at an international level has combined these products to offer a sweet snack. Secondly, the product is new and different in the sense that it does not provide too many calories nor fat, on the contrary, it provides energy and other benefits of each ingredient, in addition to its delicious flavor. According to the business line, the mission, vision and objectives of the SnacKusi company are established throughout the first 5 years of analysis, in the same way, the process flow charts and the organizational structure for the correct operation are detailed. Finally, it is carried out with financial analysis evaluating the feasibility of the project by calculating the NPV and IRR indicators, with which the viability and profitability of the project and its recovery period are demonstrated.